Preventive actions for the gradual reduction of excessive salt intake and its monitoring in Italy. (13th November 2019) - Donfrancesco, C; Bellisario, P; Galeone, D; Noce, C Lo; Russo, O; Palmieri, L; Giampaoli, S; Strazzullo, P
Abstract: Issue: The WHO Global Action Plan for the Prevention of NCDs recommends a 30% relative reduction in mean population intake of salt/sodium. To this end, the Italian Ministry of Health (MoH) has strengthened prevention and health promotion through the "Gaining health: making healthy choices easy" Programme and the National Preventive Plan (NPP) 2014-2019, with the collaboration of the Interdisciplinary Working group for Salt Reduction in Italy (GIRCSI). Description of the problem: According to the "Gaining Health" Programme, agreements between the MoH and the associations of artisan bakers and food industry companies were signed since 2009 to reduce the salt content in bread and in other food products. The reduction of excessive salt intake is one of the main objective of the NPP 2014-2019 pursued by the Regions through initiatives as local inter-sectors agreements and information activities for the population and training for food sector operators. The Italian Institute of Health conducts national surveys to estimate habitual salt intake in the general adult population by collecting 24h urine. Baseline assessment was in 2008-2012 from random samples of persons aged 35-79 years, resident in all 20 Regions. A new survey is ongoing (2018-2019) involving persons aged 35-74 years, resident in 10 Regions. Surveys are funded by the MoH-CCM; urinary sodium excretion is effected by a central lab at Federico II University of Naples, subjected to strict quality controls. Results: The baseline survey showed a mean sodium excretion of 10.6 g/24h (95% confidence interval 10.5-10.8) in 1963 men and 8.2g/24h (8.1-8.4) in 1894 women. Results of the ongoing survey are expected in the coming months. Lessons: In Italy preventive actions of salt reduction supported by the MoH have been implemented. Estimation of salt intake in diet by 24h/urine is included. Results of baseline and on-going surveys will allow to estimate the possibility of meeting the WHO salt reduction target by 2025. Key messages: In Italy inter-sectors preventive actions of salt reduction are implemented. Results of the baseline and on-going surveys will allow to estimate in Italy the possibility of meeting the WHO salt reduction target by 2025.